Analisis Pengaruh Kesadaran Merek (Brand Awareness) Pada Produk Asuransi Jiwa Prudential Life Assurance (Studi Pada Pru Passion Agency Jakarta) - Herdana, Auditya (JURNAL RISET BISNIS DAN MANAJEMEN)
This study aims to examine and analyze the effect of quality of prduct, advertising and promotion on brand awareness of Prudential Life Assurance. The data collected using questionnaire that was created based on specified indicators. The population in this study are the consumers Prudential Life Assurance. The total sample used are 100 respondents. The method of analysis used in this study is multiple linear regression. The result of the partial analysis showed that quality of product and promotion has no positive influence on brand awareness. While advertising Achievement has no positive influence on brand awareness.Keywords: Quality of Product, Advertising, Promotion, Brand Awareness